Expression of angiogenic chemokines in ovarian clear cell carcinoma. Issue 1 (29th July 2012) - Quattrocchi, Livia; Sisson, Melanie; Green, Andrew; Martin, Stewart G.; Durrant, Lindy; Deen, Suha
Abstract Aims: The aim of this study was to assess the expression of angiogenic chemokines (CXCR4/CXCL12) and the vascular endothelial growth factor in ovarian clear cell carcinoma, comparing levels against those in ovarian high‐grade serous carcinoma. Material and Methods: Tissue microarray samples from 136 cases of epithelial ovarian carcinoma (108 high‐grade serous carcinoma and 28 clear cell carcinoma) were reviewed with World Health Organization histological criteria strictly applied to categorize cases according to histological subtype. Only cases without prior exposure to chemotherapy were included. Sections were stained with vascular endothelial growth factor, CXCR4, CXCL12 and assessed using conventional histological scoring (H‐scoring). Results: Patients with clear cell carcinoma presented at an early stage of the disease (74% stage 1 and 2) and had a significantly better progression‐free (P = 0.042) survival than those with high‐grade serous carcinoma. Low expression profile of the tested markers was seen in cases of clear cell carcinoma contrary to that seen in high‐grade serous carcinoma. Conclusion: The current study reports, for the first time, the difference in expression of a set of angiogeneic prognostic markers between clear cell carcinoma and high‐grade serous carcinoma, offering a possible explanation for the apparent chemotherapy resistance. These results are relevant for the design of future clinical studies of first‐line treatment for patients with ovarian clear cell carcinoma.